WTO REFORM: BACKGROUND, CONDITIONS AND PROSPECTS - T. M. Isachenko (Vestnik MGIMO-Universiteta)
Maximizing the benefits of international division of labor and sharing the achievements of innovative development is possible only with the existence of a strict system of rules and regulations. Such system would enable fair regulation of international trade, ensure the transparency of market access and make it possible to challenge discriminatory measures, as well as to maintain certain measures to protect the interests of domestic producers. The creation of the multilateral trading system has started with the General Agreement on Tariffs and Trade (GATT) and was subsequently developed in the documents and codes, the decisions of the negotiating rounds. Since 1995, a set of rules of the World Trade Organization (WTO) became the basis of the multilateral trading system. All rules are worked out at the multilateral level. However, in recent years the negotiations within the WTO has slowed down, that affected the quality and speed of decision-making on key issues of global development. That provokes the discussion it on a certain crisis of the WTO as the main regulator of world trade, and therefore the need to provide both institutional and substantive reforms.